EVALUASI FASILITAS RUANG TUNGGU GUNA PENINGKATAN KUALITAS PELAYANAN DENGAN PENDEKATAN MAKRO ERGONOMI PADA STASIUN KERETA API XYZ - Clara Theresia; Mangara Tambunan; Nazlina Nazlina (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
A railway station XYZ is one of the business fields engaged in providing public transportation services. Service quality and its facility condition especially the waiting room still do not meet minimum standards as stateted in transportation Minister Regulation based No. PM 9 dated 8 February 2011. This research described waiting room condition through questionnaire given to the commuters. By knowing this condition, do the measurement of environmental conditions of work on the waiting room at railway station. Based on the working environmental condition in waiting room is measured. The results are a temperature range at 31-35.3oC, the illuminance level at 200-215 lux and the level of sound intensity on the waiting room range at 66.8-88.1dB. Problem solving is done by Macro Ergonomic approach by using MEAD method (Macros Ergonomic Analysis and Design) through ten process stages resulting in alternative selection that is improvement made, facility provided in the waiting room, worker’s train and social habit improvement. Work system design and waiting room facilities improvements are purposed which can be implemented by the company management in order to improve service quality.